Efektivitas Model Quantum Teaching terhadap Peningkatan Hasil Belajar IPA Siswa SDI Lopa - Dewi Rofita; Mega A. O. Jaleng; Yuliana Wahyu; Kanisius Supardi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The background of this study is the low science learning outcomes of fifth grade students of SDI Lopa, which is caused by the lack of student motivation, the use of conventional learning models, and the lack of use of learning media which causes many students to fail. The purpose of this study was to determine the effectiveness of the application of the quantum teaching model on improving the science learning outcomes of students of SDI Lopa. This study uses the Kurt Lewin design developed by Kemmis and Taggar, the main concept introduced is that in one cycle there are four components, namely planning, action, observation and reflection. The subjects of the study were fifth grade students of SDI Lopa with a total of 20 students, 9 male and 11 female. The results of the pre-action study showed that the students' science learning outcomes were low. The average class score only reached 54 and the percentage of completion was 25%. After the action was taken using the quantum teaching model in cycle I, the average class score increased to 64.2 and the percentage of completion increased to 50%. Likewise, after the improvement of quantum teaching learning in cycle II, the students' science learning outcomes were further improved. The average class score became 81.15% and the classical completion became 90%.